Effect of COVID-19 Lockdown on Health of Police Personnel in Eluru, Andhra Pradesh - Anjali Mediboina; Meghana Bhupathi (University Library System, University of Pittsburgh, 2023)
Background: COVID-19 has had an impact on all sectors of society. However, the impacts on police personnel has not been discussed enough. This study aims to identify the effects that COVID-19 lockdown duties had on the police personnel of Eluru, India. Methods: Data was collected from the available personnel in the substations of Eluru (n=82). After taking informed consent, a questionnaire was administered with three parts: A (socio-demographic details, co-morbidities information and vitals), B (DASS-21 questionnaire), and C (sleep schedule and habits). Results: Among the total respondents, 30.4% of the total respondents have significant levels of stress and 17.07% have significant levels of anxiety. Psychological impact had a positive correlation with gender, marital status and age group. Females, married officers and officers in older age groups were found to have higher levels of anxiety. Majority of the respondents got 7 hours or more sleep. The police regularly use stimulants with tea being the most common (84.1%), drinking an avg. 2 cups per day. This study found no correlation between BMI, presence of comorbidity (Hypertension, Diabetes Mellitus), and the sleeping habits with psychological impact; however, there was a notable increase in the blood pressure and blood sugar levels post-lockdown. Conclusion: Due to the retrospective nature of the study, the police personnel of Eluru have grown accustomed to the lockdown duties and appear to have developed coping mechanisms. Regardless, it is recommended to encourage further studies regarding the health of police officers and the COVID-19 impacts on the health of police personnel.